2005
DOI: 10.1073/pnas.0408304102
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for self-cleaning in gecko setae

Abstract: A tokay gecko can cling to virtually any surface and support its body mass with a single toe by using the millions of keratinous setae on its toe pads. Each seta branches into hundreds of 200-nm spatulae that make intimate contact with a variety of surface profiles. We showed previously that the combined surface area of billions of spatulae maximizes van der Waals interactions to generate large adhesive and shear forces. Geckos are not known to groom their feet yet retain their stickiness for months between mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
411
3
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 549 publications
(440 citation statements)
references
References 26 publications
13
411
3
2
Order By: Relevance
“…Both PSAs and geckos adhere primarily by van der Waals (vdW) forces (Autumn et al 2002;Creton 2003) and have effective elastic moduli below 100 kPa (Dahlquist 1969;Pocius 2002;Autumn et al 2006c), but gecko setae stand in stark contrast to PSAs in their anisotropy ) and self-cleaning (Hansen & Autumn 2005) properties. PSAs are used commonly for both industrial and home applications.…”
Section: Conventional Pressure-sensitive Adhesivesmentioning
confidence: 99%
“…Both PSAs and geckos adhere primarily by van der Waals (vdW) forces (Autumn et al 2002;Creton 2003) and have effective elastic moduli below 100 kPa (Dahlquist 1969;Pocius 2002;Autumn et al 2006c), but gecko setae stand in stark contrast to PSAs in their anisotropy ) and self-cleaning (Hansen & Autumn 2005) properties. PSAs are used commonly for both industrial and home applications.…”
Section: Conventional Pressure-sensitive Adhesivesmentioning
confidence: 99%
“…It has been suggested that this same hairy carpet on the gecko feet also plays an important role in self-cleaning. 12 Some of the other systems found in nature that exhibit self-cleaning properties are the leaves of lotus and lady's mantle plants. 18 The surface of lotus leaves have two levels of microscopic roughness ( Figure 1B).…”
mentioning
confidence: 99%
“…17 Even though the surface properties of the spatulas are not known, the hierarchical structure of gecko feet makes the macroscopic structure superhydrophobic. 12 Significant effort in developing synthetic materials inspired by gecko feet show comparable, and in some cases better, shear resistance than natural gecko feet. 2,[6][7][8][9]11 Still, these measurements were done in controlled environments and limited self-cleaning data of these synthetic materials were reported.…”
mentioning
confidence: 99%
“…7 It has also been suggested that the nanowire-structured bristles of gecko feet enable high adhesion to solid and liquid drops arising from the wetting-induced structure rebuilding of the nanowire array. 8,9 Such natural phenomena have inspired materials scientists to more closely examine the wetting behavior of fibrous media, [10][11][12][13] resulting in the development of numerous bio-inspired artificial fibrous systems with special wettability properties. To date, most endeavors have focused on developing either anisotropic fibers for water collection 4,5 and pumping 14 or a vertically aligned fiber array for controllable morphologies through capillarity-induced self-assembly.…”
Section: Introductionmentioning
confidence: 99%